International patterns and trends in ovarian cancer incidence, overall and by histologic subtype. Issue 11 (21st March 2017) - Coburn, S.B.; Bray, F.; Sherman, M.E.; Trabert, B.
Abstract : Internationally, ovarian cancer is the 7th leading cancer diagnosis and 8th leading cause of cancer mortality among women. Ovarian cancer incidence varies by region, particularly when comparing high vs . low‐income countries. Temporal changes in reproductive factors coupled with shifts in diagnostic criteria may have influenced incidence trends of ovarian cancer and relative rates by histologic subtype. Accordingly, we evaluated trends in ovarian cancer incidence overall (1973–1977 to 2003–2007) and by histologic subtype (1988–1992 to 2003–2007) using volumes IV–IX of the Cancer Incidence in Five Continents database (CI5plus) and CI5X (volume X) database. Annual percent changes were calculated for ovarian cancer incidence trends, and rates of histologic subtypes for individual countries were compared to overall international incidence. Ovarian cancer incidence rates were stable across regions, although there were notable increases in Eastern/Southern Europe (e.g., Poland: Annual Percent Change (APC) 1.6%, p  = 0.02) and Asia (e.g., Japan: APC 1.7%, p  = 0.01) and decreases in Northern Europe (e.g., Denmark: APC −0.7%, p  = 0.01) and North America (e.g., US Whites: APC −0.9%, p  < 0.01). Relative proportions of histologic subtypes were similar across countries, except for Asian nations, where clear cell and endometrioid carcinomas comprised a higher proportion of the rate and serous carcinomas comprised a lower proportion of the rate than the worldwide distribution. Geographic variation in temporal trends of ovarian cancer incidence and differences in the distribution of histologic subtype may be partially explained by reproductive and genetic factors. Thus, histology‐specific ovarian cancer should continue to be monitored to further understand the etiology of this neoplasm. Abstract : What's new? In 2012 nearly one‐quarter of a million women were diagnosed with ovarian cancer, the deadliest form of gynecological cancer. Ovarian cancer incidence and mortality rates vary, however, depending on geographical region. In this analysis of ovarian cancer by country and histologic subtype, trends in overall incidence were found to have remained stable from 1973‐77 to 2003‐07. Deviations included incidence increases in Eastern/Southern Europe and Asia and decreases in Northern Europe and North America. The distribution of epithelial ovarian cancer was similar across countries, except in Asia, where proportions of clear cell and endometrioid carcinomas were relatively high and serous carcinomas low.